Scale-Up Production of Palm-Based Wax Esters Using Lipozyme Rm Im and Characterisation of the Esters - Keng, Pei Sin (2008)
The investigation of palm-based wax esters synthesis was started in a 1-L scale stirredtank reactor (STR) with 0.5-L working volume using Rushton turbine impeller. The optimum alcoholysis conditions derived from the Response surface methodology (RSM) were: temperature 50.4°C, amount of enzyme 16 wt% of palm oil, amount of palm oil 200 mmol, amount of oleyl alcohol 600 mmol, palm oil-to-oleyl alcohol ratio 3:1 and impeller speed 242 rpm. The corresponding predicted value of percentage yield and productivity were 91.5% and 106.4 mmol/h respectively as compared to the actual experimental value of 92.3% and 110.8 mmol/h. The optimum reaction condition derived from RSM was employed in the 1.5-L STR. Rushton turbine (RT), AL-hydrofoil (AL-H) and 2-bladed elephant ear (EE) impeller were used to investigate the mixing performance in the reactor. Of these impellers, RT was found to give the highest reaction yield of 95.8% and productivity of 344.9 mmol/h at lower agitation speed (250 rpm) as compared to the other two impellers. Homogeneous solid suspension was achieved by RT impeller at 250 rpm with almost 99% solid suspension height. The shortest mixing time was obtained by the agitation system with 2-bladed EE impeller due to the larger Di/Dt ratio of the impeller. For all the impellers tested, the Reynolds number obtained were in the range of 102 <Re< 104, indicated that the fluid flow pattern fell in the transition region for the agitation range tested. Although ruptures and cracks of immobilised enzymes were observed in the agitation system, the high stability of Lipozyme RM IM was proven by its reusability of more than fifteen times under agitation system of RT impeller, to give reaction percentage yield of 78.9%, which was only 16.9% reduced from the first cycle. Subsequently, scale-up production of palm oil esters (POE) to 50-L was successfully carried out in the 75-L STR based on constant impeller tip speed method. The esters yield and productivity were increased to 97.2% and 11.67 mol/h, respectively. Higher reaction rate was observed in the 50-L scale production with the reaction equilibrium achieved earlier at 4 h of reaction time as compared to the 5 h optimum reaction time observed in bench-scale study. The esters yield and productivity were not only maintained during the scaling-up study, but increased gradually from reaction of 0.5- L, 1.5-L to 50-L. Analyses of palm-based wax esters were carried out to establish compliance to product specifications and standards. Important physicochemical properties were analysed followed a standard Test Methods modified from American Oil Chemists’ Society (AOCS) as well as Malaysian Palm Oil Board (MPOB) standard. Simultaneous differential scanning calorimetry-thermal gravimetry analysis (DSC-TGA) showed high thermal stability profile of palm-based wax esters. The dermal irritation assay of POE showed the non-irritancy of the esters with Human Irritancy Equivalent (HIE) score below 0.9; whilst an increase of skin hydration of 40.7% after 90 min application was achieved in the acute moisturising test. Downstream processing of POE was carried out using liquid-liquid extraction and crystallisation process to remove the remaining reactants including oleyl alcohol and lipids impurities in the esters. Ethanol was used as the solvent to remove the remaining unreacted oleyl alcohol in the POE mixture. The extraction was carried out in separatory funnel with optimum ethanol to esters ratio 4:1 at room temperature. A removal of 97% of the unreacted oleyl alcohol was achieved after 3 stages of extraction with 30 min contact time for each stage at 150 rpm agitation speed of the water bath shaker. Meanwhile, crystallisation of POE mixture at 23°C for 24 h incubation time was shown to increase the purity of the esters from 92.0% to 96.1%.